2001
DOI: 10.1309/nl4y-fhg8-2xbc-f9xh
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Thyroid Transcription Factor-1 in Cytologic Preparations as a Marker for Metastatic Adenocarcinoma of Lung Origin

Abstract: In tissue sections, thyroid transcription factor-1 (TTF-1) is a sensitive marker for adenocarcinomas of lung and thyroid origin. This immunohistochemical study evaluates the effectiveness of TTF-1 as a marker for pulmonary adenocarcinomas in paraffin sections of cell block preparations derived from effusion and fine-needle aspiration specimens. We evaluated 122 cell blocks including 8 primary and 39 metastatic pulmonary adenocarcinomas, 11 pulmonary neoplasms of other types, 50 specimens with nonpulmonary meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
66
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 11 publications
1
66
0
1
Order By: Relevance
“…Previously, to conduct studies related to biomarker positivity, researchers would first establish a hypothesis and verify it through clinical experiments, or conduct a long process of directly searching for, extracting, and collecting data through the hospital EMR and parsing the data before analysis [22][23][24][25]. Researchers often experience difficulties in securing such large volumes of data.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, to conduct studies related to biomarker positivity, researchers would first establish a hypothesis and verify it through clinical experiments, or conduct a long process of directly searching for, extracting, and collecting data through the hospital EMR and parsing the data before analysis [22][23][24][25]. Researchers often experience difficulties in securing such large volumes of data.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical detection for the nuclear expression of TTF-1 is considered as a useful marker in favor of lung or thyroid origin because of its high specificity (95-100%). [9][10][11][12] In the literature, TTF-1 expression in nuclei has been shown in rare cases of adenocarcinomas arising outside from lung or thyroid: one weakly positive case of metastatic ovarian carcinoma 13 and one focal positive case of endometrial carcinoma. 14 Recently, our group has shown one positive adenocarcinoma of colorectal origins, 8 whereas no such positivity was reported in literature ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…6,[19][20][21][22][23] TTF-1 positivity has also been reported in 2 of 27 ependymomas arising in the third ventricle, 24 4 of 5 invasive ductal carcinomas of the breast, 25 1 of 66 gastric cancers, 12 4 of 41 colorectal adenocarcinomas, 26 and 4 of 7 colonic adenocarcinomas. 27 In the gynecologic tract, TTF-1 expression has been noted in 2 of 166 ovarian carcinomas (1 mixed serous and endometrioid adenocarcinoma and 1 serous carcinoma) in a tissue microarray study, 10 1 of 16 ovarian cancers (cell block of cytology fluid), 11 1 of 8 endometrial cancers, 12 and 1 of 14 primary peritoneal serous carcinomas. 13 In a previous study, we identified TTF-1 immunoreactivity in 1 of 28 (4%) endocervical adenocarcinomas, 6 of 32 (19%) endometrial endometrioid adenocarcinomas, and 3 of 13 (23%) endometrial serous carcinomas.…”
Section: Ttf-1 In Ovarian Neoplasmsmentioning
confidence: 99%
“…Expression of TTF-1 has also been reported in tumors other than those originating in the lung or thyroid; however, this marker has only been studied in a few gynecologic neoplasms. [10][11][12][13] We have previously reported TTF-1 immunoreactivity in 4% (1/28) of endocervical adenocarcinomas, 16% (6/32) of endometrial endometrioid adenocarcinomas, and 23% (3/13) of endometrial serous carcinomas.…”
mentioning
confidence: 99%